Assessing Technique Applicability towards Ideation Taxonomy for Engineering Design Concept / N. M. M. Rasidi...[et al.] - M. Rasidi, N. M.; Abdullah, S.; Wahab, D.A.; Ramli, R.; M. Yassin, R. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper aims to identify students’ perception of the level of applicability of techniques that have been applied in the process of engineering design idea generation. Various techniques have been developed to facilitate the process of generating ideas. However, in generating engineering design concepts, a special technique involving the application of creative solutions and specific engineering analysis is required. This will need students to determine the appropriateness of the techniques to be adopted which will help to accelerate the process of generating ideas. This survey employed a questionnaire that was developed based on the Six P’s creativity model; and the analysis carried out using the Rasch measurement models. The respondents consist of 160 mechanical engineering students from four local universities in Malaysia that are involved in engineering design courses. The student’s data were analysed descriptively based on the frequency of use of techniques and percentage of agreement against applicability techniques. The reliability of the developed questionnaire was 0.89, while the overall five selected techniques showed an approval percentage of more than 60 percent per context. The overall findings implied that the use of a combination of creative and technical techniques helped students in the six contexts of creativity in idea generation. As a result, a hierarchy of technique application in the process of generating ideas for design engineering concept was developed. The hierarchy of techniques was used to develop a taxonomy that could serve as a reference guide for students and lecturers in the determination of the appropriateness of techniques for the aspects of what ought to be achieved in the process of generating ideas.